2021
DOI: 10.1080/00131911.2021.1931037
|View full text |Cite
|
Sign up to set email alerts
|

Embracing socioscientific issues-based teaching and decision-making in teacher professional development

Abstract: In recent decades, socioscientific issues (SSI) have been emerging from the interrelationship between science, technology, and society. For example, due to the COVID-19 pandemic, related decisions, like whether we need to ask people to use facemasks, is an SSI question being discussed internationally with no right or wrong answer. Controversial issues like SSI and the ability to make informed decisions need to be taught in school, which raises the question of whether teachers themselves are equipped with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 75 publications
(161 reference statements)
0
15
0
Order By: Relevance
“…In Han-Tosunoğlu and Özer's study (2022) on Covid-19 as a current socioscientific issue, it is seen that pre-service teachers prioritize ethical-based decision-making. Cebesoy and Chang Rundgren (2021), in their study with pre-service science teachers, examined the participants' decisions about abortion, which included three scenarios related to genetics, and the factors influencing these decisions. Contrary to the current study, Cebesoy and Chang Rungren (2021) concluded that participants attributed their decisions mostly to ethical and scientific factors.…”
Section: Discussionmentioning
confidence: 99%
“…In Han-Tosunoğlu and Özer's study (2022) on Covid-19 as a current socioscientific issue, it is seen that pre-service teachers prioritize ethical-based decision-making. Cebesoy and Chang Rundgren (2021), in their study with pre-service science teachers, examined the participants' decisions about abortion, which included three scenarios related to genetics, and the factors influencing these decisions. Contrary to the current study, Cebesoy and Chang Rungren (2021) concluded that participants attributed their decisions mostly to ethical and scientific factors.…”
Section: Discussionmentioning
confidence: 99%
“…We consider each authoritative subdimension to be students' sociocultural ways of knowing based on how they were described. Moreover, these authoritative groups have their own ideologies, consisting of values, ethics, morals, and philosophies (Betul Cebesoy & Chang Rundgren, 2021; Herman et al, 2022; Oulton et al, 2004; Rekker, 2021). For example, students referred to their political affiliations as their justifications for knowing, stating that because of their specific political group, they think a certain way.…”
Section: Discussionmentioning
confidence: 99%
“…Like political affiliations, religious practices are often deeply rooted within an individual's culture and social circles (Betul Cebesoy & Chang Rundgren, 2021). This may set an epistemic precedent of behavior and decision-making, especially from a young age (Betul Cebesoy & Chang Rundgren, 2021). Because epistemic beliefs are developed through experiences and various exposures to different knowledge sources, the authoritative presence of sociocultural groups need to be further studied, especially in the context of how students are evaluating information during SSI decision-making.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations